Rural Poverty in Developing Countries : Issues and Policies - Khan, Mahmood (Washington, D.C. : International Monetary Fund, 2000)
In most developing countries, poverty is more widespread and severe in rural than in urban areas. The author reviews some important aspects of rural poverty and draws key implications for public policy. He presents a policy framework for reducing poverty, taking into account the functional differences and overlap between the rural poor. Several policy options are delineated and explained, including stable management of the macroeconomic environment, transfer of assets, investment in and access to the physical and social infrastructure, access to credit and jobs, and provision of safety nets. Finally, some guideposts are identified for assessing strategies to reduce rural poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet